USAGE OF INTELLECTUAL TECHNOLOGY FOR AUTOMATIZATION OF TEACHING CONTROL (Journal of Information Technologies in Education (ITE), 2013)
The results of the research to identify the features usage of intellectual technologies for to realize of a synergetic model of automatization individual teaching control.
Keywords: computer aided control system for teaching; synergetic model of control; intellectual control technology